1999
DOI: 10.4269/ajtmh.1999.61.663
|View full text |Cite
|
Sign up to set email alerts
|

Interethnic differences in the humoral response to non-repetitive regions of the Plasmodium falciparum circumsporozoite protein.

Abstract: Abstract. We analyzed the humoral immune response to the amino-(amino acids 22-125) and carboxy-terminal (amino acids 289-390) non-repetitive domains of the Plasmodium falciparum circumsporozoite protein (Pf CSP) in individuals belonging to three west African ethnic groups (the Fulani, Mossi, and Rimaibé) living in the same conditions of hyperendemic transmission in a Sudan savanna area of Burkina Faso. Previous surveys conducted in the same area showed obvious interethnic differences in the susceptibility and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
33
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 29 publications
9
33
1
1
Order By: Relevance
“…The higher the parasitemia prevalence in children aged 5-14 years is therefore more likely to be related to a difference in infection risk or health-seeking behavior. This is in agreement with the observations of Snow and others, 33 and Modiano and others, 34 who found that malaria in high transmission areas affects much younger children compared with adults and those children are vulnerable to malaria infection and are therefore at risk of developing severe anemia. A higher prevalence of severe anemia in young age groups has also been reported by a study conducted in Kenya by Akhwale and others.…”
Section: Discussionsupporting
confidence: 82%
“…The higher the parasitemia prevalence in children aged 5-14 years is therefore more likely to be related to a difference in infection risk or health-seeking behavior. This is in agreement with the observations of Snow and others, 33 and Modiano and others, 34 who found that malaria in high transmission areas affects much younger children compared with adults and those children are vulnerable to malaria infection and are therefore at risk of developing severe anemia. A higher prevalence of severe anemia in young age groups has also been reported by a study conducted in Kenya by Akhwale and others.…”
Section: Discussionsupporting
confidence: 82%
“…Despite similar exposure to malaria and comparable use of protective measures, the Fulani were less parasitized and less affected by the disease. This resistance was not associated to classic malaria resistance genes (4), and the analysis of the antibody response to P. falciparum antigens revealed higher immune reactivity in Fulani than in sympatric ethnic groups (1,5,6). The hypothesis of a stronger activation of the immune system in the Fulani is also suggested by the higher frequency in this group of the tropical splenomegaly syndrome (2,7) and by the higher humoral immune response to other pathogens (Schistosoma haematobium, hepatitis B, and cytomegalovirus).…”
mentioning
confidence: 68%
“…IgG against P. falciparum CSP and MSP-1 19 were measured by ELISA as described (6). Data were compared by using the Kruskal-Wallis test.…”
Section: Quantitation Of Cytokines and Antibodiesmentioning
confidence: 99%
“…The higher incidence of spleen enlargement in the Fulani might reflect a hyper immune reactivity of this secondary lymphoid organ (Bereczky et al, 2006;Vafa et al, 2009a;Alkadarou et al, 2013), a hypothesis supported by several studies which consistently show that the Fulani mount a more robust humoral immune response, as reflected by increased titers of anti-plasmodial antibodies (Modiano et al, 1998(Modiano et al, , 1999Bolad et al, 2005;Farouk et al, 2005a;Vafa et al, 2009a). The levels of malaria blood-stage antibodies anti-AMA1 and anti-MSP1 were significantly increased in Fulani, suggesting the higher specific humoral responses against AMA1 and MSP1 in this ethnic group (Dolo et al, 2012a).…”
Section: Identification Of the Immune Mechanisms Of Resistance To Malmentioning
confidence: 92%